Perwujudan Nilai-Nilai Pancasila dalam Pembelajaran Abad Ke-21 di SMAN 14 Medan - Sunita Indira; Liesna Andriany (Universitas 45 Surabaya, 2024)
Pancasila is the entity and identity of the Indonesian nation. For this reason, Pancasila is the basis and foundation of education in Indonesia. Pancasila has unique values ​​contained in it and can be realized in 21st century learning. This research was conducted to find out how Pancasila values ​​are realized in 21st century learning both inside and outside the classroom. This research is qualitative research with observation methods carried out at SMAN 14 Medan. The results of this research show that SMAN 14 Medan has realized Pancasila values ​​in 21st century learning. These values ​​are the value of religiosity, the value of honesty, the value of responsibility, the value of civility, the value of justice, the value of unity, the value of consensus deliberation, the value of democracy, the value of social justice and the value of mutual cooperation. The realization of Pancasila values ​​is carried out side by side and mutually supports 21st century learning, namely the development of 4C skills.